2014
DOI: 10.3109/02699052.2014.888761
|View full text |Cite
|
Sign up to set email alerts
|

Versional eye tracking in mild traumatic brain injury (mTBI): Effects of oculomotor training (OMT)

Abstract: The versional-based OMT had a significant, positive effect on most aspects of versional tracking. These findings are suggestive of improved rhythmicity, accuracy and sequencing of saccades following OMT in mTBI as a result of oculomotor learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 39 publications
(77 reference statements)
2
52
0
Order By: Relevance
“…The investigators not only found improvement in symptoms but also found significant improvement in errors in horizontal vergence. 43 Cervical spine physical therapy was shown to resolve symptoms in 73% of 15 patients with mTBI compared with only 7% in a control group. 44 SUMMARY mTBI is an increasingly common public health issue.…”
Section: Diagnosismentioning
confidence: 97%
“…The investigators not only found improvement in symptoms but also found significant improvement in errors in horizontal vergence. 43 Cervical spine physical therapy was shown to resolve symptoms in 73% of 15 patients with mTBI compared with only 7% in a control group. 44 SUMMARY mTBI is an increasingly common public health issue.…”
Section: Diagnosismentioning
confidence: 97%
“…141 There is already published empirical evidence that concussion is treatable through active approaches involving earlier activity, 35 aerobic exertion, 142 vestibular, 85,132 and vision 143 therapies. Overall, these studies demonstrate that active treatments are more effective than rest-based approaches.…”
Section: Summary Of the Current Approach To Treating Concussionsmentioning
confidence: 99%
“…16,114,138 The treatment of concussion symptoms and impairments is evolving. Past practice of prolonged rest (see DiFazio et al, 2016) 50 has advanced to current hypotheses on the benefits of more active approaches to rehabilitation including vestibular, 132,144 oculomotor/vision, 143,145 and behavioral 146 therapies. Active rehabilitation involves an interdisciplinary approach directed at addressing and treating the specific, individual symptoms, impairments, and clinical profiles that may be identified at clinical presentation.…”
Section: Summary Of the Current Approach To Treating Concussionsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that 90% of patients improved markedly or completely in symptoms and subjective reports of enhanced reading at a 2-3 month follow-up. A recent study involving 12 subjects following mTBI, Thiagarajan and colleagues(77)demonstrated that an oculomotor training program targeting the version, vergence, and accommodation components of the ocular motor system significantly improved the amplitudes of vergence and accommodation, accuracy of saccadic eye movements and overall reading.…”
Section: Vestibular and Oculomotor Rehabilitationmentioning
confidence: 99%